Assessment of industrial pre-determinants for territories with active product-service innovation ecosystems. (January 2023) - Vaillant, Yancy; Lafuente, Esteban; Vendrell-Herrero, Ferran
Abstract: There has been growing interest in service-augmented products and the subsequent formation of product-service innovation (PSI) ecosystems. Hence, the objective of this paper is to empirically address an unexplored aspect of PSI ecosystems research by offering answers as to whether territories develop more performant PSI ecosystems in terms of manufacturing employment growth when they arise from an existing industrial base. Running a fixed-effects model on a sample of all 17 Spanish autonomous communities in the period from 2006 to 2012, the importance of territories having a strong incumbent manufacturing sector before developing PSI ecosystems is revealed. Specifically, it is found that PSI ecosystems will generate greater industrial employment growth in manufacturing-led territories. Our model and findings suggest various implications for scholars, managers, and policymakers alike. Highlights: The article analyses the industrial pre-determinants of product-service innovation (PSI) systems. The theoretical premiss of territorial servitization are empirically sustained. Territories develop more performant PSI ecosystems in terms of manufacturing employment growth when they arise from an existing industrial base. Solid PSI systems are built upon a resilient manufacturing base in territories with a historical industrial trajectory.